Indonesian National Development Planning System Based on State Policy Guidelines (GBHN) : A Return to the Future? - Hilaire Tegnan; Charles Simabura; Saldi Isra (UNISSULA, 2018)
The National Guidelines of State Policy known to the Indonesian people as Garis Besar Haluan Negara (GBHN) used to be a set of political, economic and social principles enacted every five years by the People’s Consultative Assembly or Majels Permusyawaratan Rakyat (referred to as MPR hereafter) that had to be followed by both central and regional governments for the prosperity of Indonesia and the Indonesian people. However, since the amendments to the 1945 Constitution (1999-2002), which stripped MPR of much of its power, this national development planning scheme was abolished and decentralization was established throughout Indonesia. Nevertheless, in recent years more voices are being heard demanding the reinstatement of the National Guidelines. This paper discusses the issue of national development planning at the central government level. Drawing on the example of the Indonesian National Guidelines of State Policy, the paper argues that a possible return to the old guideline policy could be counter-productive as it would harm the decentralization process, political freedom, democracy, human rights, and the rule of law in Indonesia.